Enhanced thermoelectric performance of solution-grown Bi2Te3 nanorods. (September 2021) - Tarachand,; Saxena, M.; Okram, G.S.; Lakhani, A.; Kuo, Y.-K.; Tyagi, S.; Behera, P.; Bhalerao, G.M.; Sathe, V.; Deshpande, U.
Abstract: The dominant role of trioctylphosphine (TOP) on the precise crystallite size and enhanced thermoelectric (TE) performance of the solution-grown Bi2 Te3 nanorods annealed at 250 °C for 5 h under Ar gas flow and pelletization under 1 GPa pressure at 27 °C only has been demonstrated here. This has resulted in systematic reduction of crystallite size (D), emergence of a secondary phase BiTe with increasing TOP, and enhancement in thermopower but drastic drop in thermal conductivity due to atomic-scale control over the grain size and boundaries. The highest ZT and power factor (PF) obtained for nanorods with D = 40 nm are 1.95 and 1.4 times higher than those of D = 63 nm are due to the optimum intergrain energy barrier height for filtering of the charge/heat carriers. Remarkably, this enhanced ZT/PF is promisingly greater than those of the other more sophisticatedly solution-processed samples reported earlier. Moreover, the IR-active A1u modes in Raman spectra of nanorods of centrosymmetric Bi2 Te3  have been observed for the first time with TOP-induced reduction of D confirming the breaking of crystal inversion symmetry due to the formation of sub-quintuples. Thus, this grain size alteration strategy for ZT improvement will open a new vista for further development of Bi2 Te3 -based efficient TE materials near room temperature. Graphical abstract: There is dominant role of trioctylphosphine (TOP) on the precise crystallite size control, emergence of a secondary phase BiTe with increasing TOP, observation of the IR-active A1u modes in Raman spectra of nanorods of centrosymmetric Bi2 Te3 for the first time on breaking of crystal inversion symmetry due to the formation of sub-quintuples, and enhanced thermoelectric performance of the solution-grown Bi2 Te3 nanorods annealed at 250 °C for 5 h under Ar gas flow and palletization under 1 GPa pressure at 27 °C only with the highest ZT and power factor greater than those of the other more sophisticatedly processed samples reported earlier. Image 1 Highlights: A precise control of crystallite size (D) of Bi2 Te3  improves its thermoelectric performance near room temperature. Filtering of charge/ heat carriers leads to simultaneous reduction in lattice thermal conductivity and enhancement in thermopower. Trioctylphosphine-induced reduction of D demonstrates breaking of crystal inversion symmetry in centrosymmetric Bi2 Te3 .